The Effect of Fermented Goat's Biourine Dose on Growth and Yield of Beans (Phaseolus vulgaris L.) - Retno Tri Purnamasari; Ratna Zulfarosda (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2019)
This research aim to determine the effect of fermented goat's biourin dose on growth and yield of beans. The research was conducted in Krapyakrejo Village, Gadingrejo District, Pasuruan at an altitude of 5 m above sea level in March - May 2018.The research used a randomized block design and repeated five times, the treatment was a fermented goat’s biourin dose consisting of five levels: P0 (Control) : ZA 300 kg/ha, SP36 200 kg/ha, KCl 100 kg/ha; P1: POC 1.500 l /ha + ZA 300 kg /ha, SP36 200 kg/ ha, KCl 100 kg/ha; P2: POC 2.000 l ha + ZA 300 kg/ha, SP36 200 kg/ha, KCl 100 kg/ha; P3: POC 1.500 l/ha + ZA 150 kg/ha, SP36 100 kg/ha, KCl 50 kg/ha and P4: POC 2.000 l/ ha + ZA 150 kg/ha, SP36 100 kg/ha, KCl 50 kg/ha.The results showed that beans with higher yields were found in POC 2.000 l/ha and inorganic half-dose treatment which produced 26,01 tons/ha, POC 2.000 l ha and full-dose inorganic produced 24,53 tons/ha, POC 1.500 l/ha and full-dose inorganic produced 24,29 ton/ha, POC 1.500 l/ha and inorganic half dose produced 23,56 ton/ha and controls give lower yields, 22,94 tons/ha.